Psychometric properties of the Chinese version of the Family Questionnaire among the caregivers of people with schizophrenia - Peng, Yanan; Xiong, Enhe; Li, Yan; Song, Lanjun; Xi, Juzhe (Frontiers in Public Health, 2023)
Introduction Expressed emotion refers to relatives' attitudes and emotional behaviors toward mentally ill family members. It is a robust predictor of patients' illness outcomes and caregivers' wellbeing in a wide range of mental disorders. However, expressed emotion has not been fully explored in the Chinese context. One reason is the lack of reliable and cost-effective measurements. A reliable, valid, and user-friendly instrument is needed to support the research and clinical practice based on expressed emotion in China. This study aimed to translate, adapt, and examine the psychometric properties (factorial structure, measurement invariance, internal consistency reliability, and concurrent validity) of a Chinese version of the Family Questionnaire. Methods A total of 248 caregivers participated in the study. A translation and back-translation procedure was applied to translate the Family Questionnaire into Chinese. We compared two models to examine the factor structure of the questionnaire by performing confirmatory factor analysis. We also conducted measurement invariance analysis to test whether the factor structure of the tool is invariant across male and female groups. Reliability was evaluated with Cronbach's α. The concurrent validity was examined by testing the predictivity of the expressed emotion on relevant outcomes with path analysis. We used the STROBE checklist to report. Results The item-total correlation coefficients of the scale ranged from 0.375 to 0.752. The confirmatory factor analysis indicated that the Chinese version of the Family Questionnaire displays the original two-factor structure (emotional overinvolvement and criticism; X2 = 335.50, df = 169, X2/df = 1.985, RMSEA = 0.063, SRMR = 0.058, CFI = 0.913, and TLI = 0.902). In addition, the two-factor structure was invariant across the male and female groups. The two subscales showed excellent internal consistency, with Cronbach's alpha of 0.92 for both emotional overinvolvement and criticism. The concurrent validity of the Chinese version was supported by the good predictivity of the two subscales to care burden, family function, and quality of life. All path coefficients were significant, and the absolute values of path coefficients ranged from 0.23 to 0.72. Conclusion The Chinese version of the Family Questionnaire is a valid and reliable measurement of expressed emotion in the Chinese context.